Metallicities in long gamma-ray burst host galaxies at z < 0.5 calculated by the detailed modelling of optical and infrared line ratios. Issue 3 (20th January 2017) - Contini, M.
Abstract: We revisit the line spectra emitted from long gamma-ray burst (LGRB) host galaxies at z ≤ 0.5 in order to calculate, through the detailed modelling of line ratios, the physical conditions and relative abundances in LGRB hosts in this redshift range. We have found lower metallicities than in LGRB hosts at higher z . New results regarding the metallicities and physical conditions in different regions throughout the LGRB 980425 host at z  = 0.0085 are presented. In particular, we have found that the effective starburst temperature in the supernova (SN) region is the highest in the entire host galaxy. The low ionization parameter reveals that the radiation source is far away, or is somehow prevented from reaching the emitting gas in the SN region. Models constrained by a few oxygen, nitrogen and sulphur line ratios to Hβ in the LGRB 980425 host reproduce the He ii /Hβ and [Ar iii ]/Hβ line ratios satisfactorily. Modelling of the observed [S iv ]10.51 μm/[S iii ]18.71 μm and [Ne iii ]10.6 μm/[Ne ii ]12.81 μm line ratios from the LGRB 031203 host galaxy at z  = 0.105 shows that the mid-infrared lines are emitted from geometrically thin shock-dominated filaments that are not reached by photoionizing flux, while the optical lines are emitted from radiation-dominated outflowing clouds.